Current status and future perspectives of the diagnostic of plant bacterial pathogens - Wang, Xu; Liang, Shuiying; Gan, Qinhua; Cai, Bo; Liu, Caixia (Frontiers in Plant Science, 2025)
Diagnostic of plant bacterial pathogens underwent a leapfrog development from culture-based strategies to culture-free detection. Conventional diagnostics, such antibody- and PCR-based methods, are sensitive to identify pre-enriched pathogens in naturally infected crops at the late stage. However, they suffer from shortcomings relating to rapidity, signal strength, and a significant reduction in sensitivity in real plant extract. Progress has been made to address these challenges through development of labelled and non-labelled optical spectroscopy. Specifically, the micro-Raman spectroscopy enables fast, label-free, and non-invasive discrimination of viable but non-culturable pathogens at a single-cell level. A comprehensive spectroscopic database is always a prerequisite for identification, yet these spectroscopy-based methods are insufficient to detect previously unknown plant pathogens. The advance of single-cell sequencing and synthetic biology is beginning to address these crucial problems and is being used in related practical applications. Success will continue to be found at the interfaces between disciplines.